Analisis Evaluasi Tarkib dan Mufradat di Soal Ujian Madrasah Bahasa Arab MA TP 2020-2021 dan TP 2021-2022. - Ibadurrahman; Asmal May; Hikmah (INTIFA: Journal of Education and Language, 2024)
This content analysis aims to analyze the comparison of the content of the tarkib and mufrodat evaluations on the MA Arabic Madrasah Exam questions for the 2020-2021 academic year with the 2021-2022 academic year. The method used in this research is analysis with a qualitative research approach. The type of research used is descriptive research using documentation techniques. From the results of the analysis of the 2020/2021 questions, the researchers found that there were 24 questions about the tarkib, and there were 16 questions about the mufrodat, and from the results of the analysis about the questions for 2021/2022, the researchers found that the questions about the tarkib were 16 questions, and the questions about the mufrodat were 5 questions. Abstrak Analisis isi ini bertujuan untuk menganalisis perbandingan muatan evaluasi tarkib dan mufrodat pada soal Ujian Madrasah Bahasa Arab MA Tahun Pelajaran 2020-2021 dengan Tahun Pelajaran 2021-2022. Metode yang digunakan dalam penelitian ini adalah analisis dengan pendekatan penelitian kualitatif. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan menggunakan teknik dokumentasi. Dari hasil analisis soal tahun 2020/2021, peneliti menemukan soal tarkib berjumlah 24 soal, dan soal mufrodat berjumlah 16 soal, dan dari hasil analisis soal tahun 2021/2022, peneliti menemukan soal tarkib berjumlah 16 soal, dan soal mufrodat berjumlah 5 soal.